Energy management study in indoor farming plant factory - Shaari, Abdul Muin (2022)
This thesis reports the energy efficiency study conducted in two distinct indoor farming facilities namely the AgroCube (the container type of indoor farming facility) and the plant factory (commercial scale indoor farming facility). Both of these facilities were owned by Malaysian Agricultural Research and Development Institute (MARDI) which are located in Serdang, Malaysia. This pioneering study is important to establish the unique energy profile of indoor farming facilities as well as analysing the specific energy consumption of crops produced. Both of these findings are vital in further improving the present energy use as well as reducing overall operational costs. Therefore, this was carried out in these facilities involving walk-through audit, electrical power logging for a duration of one week to establish their load profiles and identifying the significant energy users (SEUs), energy analysis and finally the specific energy consumption of the crops produced. The load profiles for LED lighting system, water pump, air conditioning system and other smaller electrical equipment were distinguished during this study. The load profile, total power demand, average demand and peak demand were obtained and used to calculate the specific energy consumption of the crop. From the energy apportioning, it was found that the total energy consumption during 1 week for AgroCube is 414.153kWh while for the MARDI’s plant factory is 3788.423kWh. The specific energy consumption for the AgroCube was 17.15kWh/kg and 19.2kWh/kg for the MARDI’s plant factory. Several possible strategies for saving energy for all term were proposed to further improve these values based on operational requirements by MARDI including payback period. For both of the plant factory, the significant strategies for short term is to turn off air-conditioner during low consumption, medium term is to switch to inverter air-conditioner and for long term is integration with solar energy.